2016
DOI: 10.1159/000444251
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Kidney Stone in a Kidney-Transplanted Patient with Mini-Percutaneous Laser Lithotripsy: A Case Report

Abstract: We report a case of a kidney-transplanted patient with urolithiasis treated with mini-percutaneous laser lithotripsy. The patient presented with renal dysfunction and graft hydronephrosis. Diagnostic procedures revealed ureterolithiasis as a cause of obstruction, and percutaneous nephrostomy was inserted as a temporary solution. Before surgery, the stone migrated to the renal pelvis. Mini-percutaneous laser lithotripsy was successfully performed, and during surgery, all stone fragments were removed. Six months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
1
6
0
4
Order By: Relevance
“…Furthermore, because of the relative superficial position of transplanted kidneys, percutaneous management is favored. Indeed PCNL has the best success rate, but it is an invasive procedure on a single functioning kidney (14). Krambeck, who described the largest series of PCNL in transplant kidneys, reported perioperative complications in about ¼ of patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because of the relative superficial position of transplanted kidneys, percutaneous management is favored. Indeed PCNL has the best success rate, but it is an invasive procedure on a single functioning kidney (14). Krambeck, who described the largest series of PCNL in transplant kidneys, reported perioperative complications in about ¼ of patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…For larger calculi, percutaneous nephrolithotomy (PCNL) can be performed via easy access because of the position of the allograft in the iliac fossa and the short puncture distance between skin and renal pelvis [ 85 , 86 ]. Using mini- PCNL, the tissue damage to the graft can be reduced [ 87 ]. In 2018, Emiliani et al reported that in 51 cases of urolithiasis therapies in transplanted kidneys including active surveillance, ante- and retrograde ureteroscopy, ESWL, PCNL and the open approach they found no loss of renal function through intervention and no case of allograft loss [ 88 ].…”
Section: Endoscopic Management Of Postoperative Urologic Complications In Kidney Allograft Recipientsmentioning
confidence: 99%
“…U današnje vrijeme se u liječenju urolitijaze u transplantiranih pacijenata, kao i u standardne populacije, koriste minimalno-invazivne metode. Ove metode uključuju ureterorenoskopiju (prvenstveno fleksibilnu ureterorenoskopiju), perkutanu nefrolitotripsiju i ESWL 42,[44][45][46][47] . U manjeg broja pacijenata urolitijaza se rješava laparoskopskim ili otvorenim pristupom.…”
Section: Ispitanici I Metodeunclassified